'People with learning disabilities need a commissioner and a legal charter of rights' – no they do not!. Issue 3 (15th March 2016) - Richards, Michael
Abstract: Since the UK Winterbourne View scandal, there have been a number of reports and responses recommending what should be done to ensure a similar scandal does not happen again. Two ideas have emerged which suggest that people with learning disabilities need a legal charter of rights and a commissioner to make a difference in their lives. This article, however, argues that although it is right that issues affecting people with learning disabilities are at the heart of discussion and debate, this does not take into account the complex, flexible and multiple identities of people with learning disabilities, and their knowledge, experiences and skills. This would be more beneficial in understanding the lives of people with the label of learning disabilities than a commissioner or a charter.